Protein Normalization in Different Adipocyte Models and Dependence on Cell Size - Matthae, S.; May, S.; Hubersberger, M.; Hauner, H.; Skurk, T. (Hormone and Metabolic Research, 2013)
Various in vitro models are commonly used to study adipose tissue function. However, methods for protein normalization in dependence of differentiation and fat cell size are poorly defined. Therefore, the aim of this study was to characterize frequently used housekeepers during adipose differentiation in fat cells of varying cell size and between different subjects to allow a reliable and robust data interpretation. Human preadipocytes, SGBS, 3T3-L1, and mature cells were used to study the housekeeper profile. Glyceraldehyde-3-phosphate dehydrogenase was the most stable internal control in human preadipocytes, whereas all others showed substantial variation. In SGBS and 3T3-L1 cells none of the housekeepers revealed stable protein levels during differentiation. In mature adipocytes GAPDH and α-tubulin were found to be suitable as internal loading controls. Importantly, there was no substantial variation between different donors. However, Coomassie-staining turned out to represent an appropriate alternative as a stable and highly sensitive internal standard for all cell models tested. In conclusion, standard housekeeping proteins have substantial limitations in studies of adipogenesis and in dependence of fat cell size. Coomassie-staining turned out to be a sensitive and stable alternative as internal control for western blot studies during adipogenesis. However, inter-subject variability was low for the investigated housekeeper.
Keywords: western blot; reference gene; adipogenesis; fat cell size